Collagen VI as a driver and disease biomarker in human fibrosis. (14th June 2021) - Williams, Lynn; Layton, Thomas; Yang, Nan; Feldmann, Marc; Nanchahal, Jagdeep
Abstract : Fibrosis of visceral organs such as the lungs, heart, kidneys and liver remains a major cause of morbidity and mortality and is also associated with many other disorders, including cancer and metabolic disease. In this review, we focus upon the microfibrillar collagen VI, which is present in the extracellular matrix (ECM) of most tissues. However, expression is elevated in numerous fibrotic conditions, such as idiopathic pulmonary disease (IPF), and chronic liver and kidney diseases. Collagen VI is composed of three subunits α1, α2 and α3, which can be replaced with alternate chains of α4, α5 or α6. The C‐terminal globular domain (C5) of collagen VI α3 can be proteolytically cleaved to form a biologically active fragment termed endotrophin, which has been shown to actively drive fibrosis, inflammation and insulin resistance. Tissue biopsies have long been considered the gold standard for diagnosis and monitoring of progression of fibrotic disease. The identification of neoantigens from enzymatically processed collagen chains have revolutionised the biomarker field, allowing rapid diagnosis and evaluation of prognosis of numerous fibrotic conditions, as well as providing valuable clinical trial endpoint determinants. Collagen VI chain fragments such as endotrophin (PRO‐C6), C6M and C6Mα3 are emerging as important biomarkers for fibrotic conditions. Abstract : Collagen VI plays an important role in organizing three‐dimensional tissue architecture. However, its expression is elevated in numerous fibrotic diseases such as NASH and IPF, specifically associating around myofibroblast‐rich fibrotic foci. Enzymatic cleavage of collagen VI leads to the release of bioactive peptides, which exacerbates the fibrotic process. These peptides enter the systemic circulation where their levels can be used to monitor the stage and progression of fibrotic diseases.